화재 시 재실자 행동의 상호 작용을 고려한 건물 피난 행태 분석 - 최민지; 박문서; 이현수; 황성주; Choi, Minji; Park, Moonseo; Lee, Hyun-Soo; Hwang, Sungjoo (한국건설관리학회 논문집, 14(6), 2013)
Evacuation process has been considered as one of the most important elements to be managed in public facilities. Although the importance is highlighted through numerous literatures, disaster evacuation planning, particularly fire accidents, faces a number of human behavior related limitations for a similar application to different types of facilities/occupants. To overcome the obstacles including complexity in human behaviors, a number of simulation techniques with limited consideration on human behaviors are utilized to predict foreseeable problems in evacuation process. Therefore, this research aims to propose system dynamics models incorporating human behaviors considering different types of occupants under disaster evacuation events. Analysis on emergent human behaviors such as group forming and interactions under urgent situation are conducted based on the main stream theories in social science field. The results suggest the influences of human behavior factors including cooperative intention, information sharing, and mobility change to evacuation behavior. The implications are expected to provide safety consideration at planning/designing phase of buildings and help facility safety managers for evacuation planning with more realistic management approaches. 건축물에 있어 피난 계획은 프로젝트 전반에 걸쳐 고려되어야 할 매우 중요한 요소 중 하나이다. 기존 다양한 연구 및 실제 재난 사례등을 통해 피난의 중요성은 지속적으로 강조되어 왔으며, 사전 대비를 위한 다양한 노력들이 수행되어 왔다. 또한, 실제와 유사한 대응 훈련 준비의 어려움을 극복하고자 시뮬레이션을 통한 해결책 마련이 새로운 대안으로 떠올랐다. 그러나 피난 계획의 경우 시설물 뿐만 아니라 재실자의 특성 또한 신중히 고려되어야 한다. 현실과 가까운 피난 계획의 수립을 위해 본 연구에서는 인간 행태를 고려한 피난 과정을 분석한다. 기존 사회과학 이론에 기초하고 시스템 다이내믹스 모델링을 이용하여, 피난 초기부터 탈출까지 다양한 재실자 그룹의 특성으로 인해 발생하는 요인들을 포함하며, 이에 따른 의사결정, 행동의 변화 등의 분석한다. 이러한 모델을 통해 그룹 형성 및 재실자 간 상호 작용 등 긴급 상황에서 발생하는 인간 행태가 전체 피난 행태 및 결과에 미치는 영향을 파악하며, 향후 피난 시뮬레이터의 모듈로써의 활용 및 시설물 안전 관리자의 피난 계획 수립 시 의사결정의 기초자료를 제공할 것이라 예상된다.